ANALISIS IMPLEMENTASI STANDAR AKUNTANSI KEUANGAN ENTITAS TANPA AKUNTABILITAS PUBLIK (SAK ETAP) PADA UMKM (STUDI KASUS USAHA LADU ARAI PINANG â€œRANIâ€) - Salfina, Lili; Febriani, Ayu; Oktaviani, Nichy (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2019)
This research aimed to know the implementation about Financial Accounting Standards Entities Without Public Accountability (SAK ETAP) of Keripik Ladu Arai Pinang â€œRANIâ€ SMEs in Pariaman City. The method used in this study is qualitative approach. This research uses primary data source and secondary data source. The primary data source in the form of information and data supplied by the owner SMEs, while secondary data source are from website, and documents that support. Data collection techniques using triangulation techniques, namely the interview, documentation and observation. Data analysis techniques with data reduction, data display and conclusion. Based on the research in mind that Business Ladu Arai Pinang â€œRANIâ€ SMEs have not record based SAK ETAP. Therefore, researchers have drafted of the financial statement based SAK ETAP, include balance sheet, income statement, capital statement, cash flow statement and notes of financial statement. Financial statement SMEs made the researcher based on information obtained during the research, then processed into financial statement based SAK ETAP.